2007
DOI: 10.2340/00015555-0285
|View full text |Cite
|
Sign up to set email alerts
|

"Videoconferencing Journal Club for Dermatology Residency Training: An Attitude Study

Abstract: The use of videoconferencing as a teaching modality in dermatology is not widespread. The objectives of this study were to introduce the videoconferencing format to dermatology journal clubs and to determine its effects on the training and satisfaction of house officers (residents). Ten dermatology house officers participated in this study. They were being trained at three university hospitals in rotation. A videoconferencing facility maintained by the hospitals for remote conferencing was used. After completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…8 It is a useful adjunct to traditional education and provides opportunities for participants in rural and remote areas who, due to time, travel, and cost constraints, would normally be unable to participate. 9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…8 It is a useful adjunct to traditional education and provides opportunities for participants in rural and remote areas who, due to time, travel, and cost constraints, would normally be unable to participate. 9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…To this end, videoconferencing has proven to be a useful mechanism for small group learning whereby learners are located remotely and the facilitator is at a central, often academic, site. This approach has been particularly meaningful for addressing the educational needs of learners in underserviced areas (Ahn et al 2007;Holland et al 2008). For example, Allen et al (2003) assessed the use of videoconferencing for post-graduate education using small group learning with physicians in Nova Scotia, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…When asked about their impression of the training program on health hearing, there was almost a draw between satisfied and very satisfied ACS (51 to 48%).International studies 16,17 show that this method is useful and broadly used in health care, which shows participants satisfaction in general terms. In Brazil, a 2010 18 study showed that ACS's opinion about videoconference for health hearing training was welcome and met the Ministry of Health's requirements, which has taken measures to assist Family Health teams to provide full and quality care to the Brazilian population.…”
Section: Resultsmentioning
confidence: 99%